2018
DOI: 10.1002/hbm.24070
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study of finger tapping in children and adults

Abstract: Functional brain imaging studies have characterized the neural bases of voluntary movement for finger tapping in adults, but equivalent information for children is lacking. When contrasted to adults, one would expect children to have relatively greater activation, reflecting compensation for an underdeveloped motor system combined with less experience in the execution of voluntary movement. To test this hypothesis, we acquired functional magnetic resonance imaging (fMRI) data on 17 healthy right-handed childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 50 publications
(98 reference statements)
8
31
1
Order By: Relevance
“…The greater contralateral SM1 activation in children than in adults (Fig. ) is in line with previous reports from other unimanual finger tapping tasks (De Guio et al , ; Turesky et al , ). Exact neuronal underpinning of this phenomenon is still unknown; however, the extensive activation in children might reflect their broader index finger representation in the SM1 as their somatotopical representations are likely under development (Nebel et al , ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The greater contralateral SM1 activation in children than in adults (Fig. ) is in line with previous reports from other unimanual finger tapping tasks (De Guio et al , ; Turesky et al , ). Exact neuronal underpinning of this phenomenon is still unknown; however, the extensive activation in children might reflect their broader index finger representation in the SM1 as their somatotopical representations are likely under development (Nebel et al , ).…”
Section: Discussionsupporting
confidence: 91%
“…Since a BOLD signal reflects synaptic activity (Logothetis et al , ), the present age‐dependent attenuation of SM1 activation could be associated with an age‐dependent increase in synaptic efficiency in the contralateral (left) M1 hand section through the long‐term use of right hand fingers during routine daily manual tasks. This view is compatible with the idea that greater neuronal resources (e.g., synaptic inputs) are generally required in children performing the same task as adults (De Guio et al , ; Turesky et al , ). If our view is correct, the smaller and weaker BOLD signal in the SM1 during a motor task is not specific to pianists’ and athletes’ brains, but is also observable in typical human development.…”
Section: Discussionsupporting
confidence: 80%
“…We may attribute this discrepancy to differences in the task. Both of the present and previous tasks included a timing motor-control component because the tasks consistently asked the participants to generate a movement at a given time [1 Hz in the present study, 2 Hz in De Guio et al ( 2012 ), and either 0.87, 1.11, or 1.54 Hz in the study by Turesky et al ( 2018 )]. On the other hand, our task required the participants to keep controlling the alternating extension–flexion movements of the wrist, while the previous tasks required simple button presses with the index finger (De Guio et al 2012 ) or the thumb (Turesky et al 2018 ).…”
Section: Discussionmentioning
confidence: 94%
“…For example, it has been demonstrated that, in the human brain, the grey matter maturation of the primary sensorimotor cortex (SM1) occurs relatively earlier in the entire brain, in addition to the occipital visual cortex (Gogtay et al 2004 ). Moreover, it has been demonstrated that 6- to 13-year-old children and adolescents already exhibit activation in the cerebrocerebellar sensorimotor network between the contralateral SM1 and the ipsilateral cerebellar hemisphere (lobules V and VI) when they performed finger-tapping tasks with their right hands, with some quantitative difference from adults (De Guio et al 2012 ; Turesky et al 2018 ). Furthermore, we previously demonstrated that 8- to 11-year-old children recruit the cerebrocerebellar sensorimotor network during kinesthetic (muscle spindle afferent) processing of the right hand (Naito et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile EEG systems enable to record brain activity during active movement thus allowing for the measurement of highly ecologically valid neurophysiological signals. Until recently, research on the neural correlates of motor behavior relied mostly on artificial settings investigating, e.g., finger tapping tasks with low ecological validity using stationary EEG or fMRI systems (e.g., Turesky et al, 2018;Schmitz et al, 2019). Mobile EEG systems tackle these shortcomings by allowing for more naturalistic behavior during physiological recordings (Gramann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%